Finite element analysis of elastomeric bearings under cyclic shear loading - Biçer, Berkay. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2023., 2023)
The study is concerned with the analysis of high damping rubber isolation bearings under seismic excitations. High damping rubber (HDR) plays an important role in seismic isolation systems due to its good damping capability and long service life. Accurate representation of its mechanical behavior is essential for the simulation of the high damping rubber bearings (HDRB). The emphasis of the study is on the formulation of a constitutive model for HDR that accounts for large strains, cyclic loading, hysteresis and rate dependence while being computationally efficient. The calibration of the constitutive model and its validity are done using experimental data available in the literature. The constitutive model for HDR is used in the analysis of HDRB. 2D and 3D finite element models of bearing are developed and the response for compression and shear loadings are predicted. The sensitivity of the response to various parameters is investigated. The agreement of the predictions with the limited test data on HDRB is encouraging. Bearing stiffness and damping ratio are calculated within ranges available in the literature. The effect of loading rate on the hysteresis amount follows the trend observed in experiments. The methodology developed in the thesis can be applied to different isolators. The computational model can be used to understand the isolator’s behavior in detail without numerous tests and procedures.
Keywords: Elastomers.; Rubber bearings.; Seismic waves -- Damping.